Τhe association of heart failure across left ventricular ejection fraction with mortality in atrial fibrillation. (3rd June 2021) - Kartas, Anastasios; Samaras, Athanasios; Akrivos, Evangelos; Vrana, Eleni; Papazoglou, Andreas S.; Moysidis, Dimitrios V.; Papanastasiou, Anastasios; Baroutidou, Amalia; Botis, Michail; Liampas, Evangelos; Vouloagkas, Ioannis; Karagiannidis, Efstratios; et al.
Abstract: Aims: The aim of this study is to investigate the prognostic implications of the presence of heart failure (HF) across the range of left ventricular ejection fraction (LVEF) in patients with comorbid atrial fibrillation (AF). Methods and results: We conducted a retrospective cohort study of 1063 patients (median age 76 years), discharged from the cardiology ward with a primary or secondary diagnosis of AF between 2015 and 2018. We used Cox proportional‐hazards and spline models to examine the association of the presence of HF, across the range of LVEF, with the primary outcome of all‐cause mortality. HF was documented in 52.9% of patients at baseline. During a median follow‐up of 31 months (interquartile range 10 to 52 months), 37.3% of patients died. The presence of HF was associated with a significantly higher risk of mortality [adjusted hazard ratio (aHR) 2.17; 95% confidence interval (CI), 1.70 to 2.77; P < 0.001], which was evident across HF with reduced (aHR 3.03; 95% CI 2.41 to 4.52), mid‐range (aHR 2.08; 95% CI 1.47 to 2.94), and preserved LVEF (aHR 1.94; 95% CI 1.47 to 2.55). Among patients with HF, the spline curve depicted a non‐linear association between LVEF and the risk of death, in which there was a steep and progressive increase in mortality for every 5% reduction in LVEF below 25% (aHR 1.97, 95% CI 1.04 to 3.73, P = 0.04). Conclusions: In patients with AF who were discharged from the hospital, the presence of HF at baseline was independently associated with a twofold risk of death, which was significant across LVEF‐classified HF subtypes. Among patients with AF and HF, the risk of death rose significantly as LVEF was reduced below 25%.